BULLYING SEBAGAI CARA UNTUK MENGAKRABKAN (STUDI FENOMENOLOGI DI KALANGAN SISWA SMA KOTA KUPANG) - Arman Rifat Lette; Aysanti Yuliana Paulus (Excellent Midwifery Journal, 2022)
Bullying behavior or violence in schools was still happening today. There have been many studies related quantitatively to describe bullying behavior but not many have studied it qualitatively from the perspective of students as perpetrators and victims, especially in Kupang City. This study aimeds to describe bullying behavior among high school students in Kupang City. The research method was qualitative research with an exploratory design and a phenomenological approach. The main informants were high school students in 2 different schools. Supporting informants were subject teachers, teachers in the student section and the principal. There was 12 informants. Data collection was carried out by means of Focus Group Discussion (FGD) and in-depth interviews. The study was conducted from June-September 2020. The results showed that bullying was considered as joke and can make friends, bullying behavior also often occurs, namely: Joking and sarcastically ending up in a fight, calling by a pseudonym or animal name, Bullying as an outlet because lack of attention from parents, bully retaliating and fighting for strength in the classroom and bullying is taken casually/considered normal. It was necessary to do Communication, Information and Education to students so that they do not take bullying behavior as usual because of the real negative impact that occurs among school students. The role of family and school were also very important in preventing bullying among students.